2006
DOI: 10.4490/algae.2006.21.1.141
|View full text |Cite
|
Sign up to set email alerts
|

Growth Characteristics, Bio-chemical Composition and Antioxidant Activities of Benthic Diatom Grammatophora marina from Jeju Coast, Korea

Abstract: Benthic diatoms are known as a good food for shellfish in nature and in commercial hatchery of Jeju Island, Korea. Grammatophora marina is commonly found as dominant benthic micro-algae in Jeju coastal waters throughout the year. To know the best growth conditions of this species, culture was done in terms of three parameters; water temperature, salinity and nutrients. Each parameter was controlled by temperature of 15, 20 and 25°C; salinity of 25, 30 and 35 psu; and nutrient concentrations of 50, 100 and 200%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…Similar observations have been reported by different authors (e.g. Nagayama et al, 2003;Affan et al, 2006;Goh et al, 2010) and are consistent with the fact that microalgae, and in particular diatoms, bear a number of antioxidant compounds, including carotenoids, polyunsaturated fatty acids and polysaccharides (Mohamed, 2008;Holtin et al, 2009;Scholz et al, 2014). In contrast, both the long-term UV-B-and combined UV-treatments of the five diatom taxa showed significant correlations between the DPPH and FRAP assays and the total phenolic contents (P < 0.05), suggesting that phenolic compounds could be involved in acclimatization to at least UV-B long-term exposure.…”
Section: Relationship Between Phenolic Compounds and Antioxidant Capasupporting
confidence: 93%
See 2 more Smart Citations
“…Similar observations have been reported by different authors (e.g. Nagayama et al, 2003;Affan et al, 2006;Goh et al, 2010) and are consistent with the fact that microalgae, and in particular diatoms, bear a number of antioxidant compounds, including carotenoids, polyunsaturated fatty acids and polysaccharides (Mohamed, 2008;Holtin et al, 2009;Scholz et al, 2014). In contrast, both the long-term UV-B-and combined UV-treatments of the five diatom taxa showed significant correlations between the DPPH and FRAP assays and the total phenolic contents (P < 0.05), suggesting that phenolic compounds could be involved in acclimatization to at least UV-B long-term exposure.…”
Section: Relationship Between Phenolic Compounds and Antioxidant Capasupporting
confidence: 93%
“…(e.g. Affan et al, 2006;Goh et al, 2010). According to Hanaa et al (2008) these compounds are extracted by dichloromethane and might contribute to the high scavenging activities found in the present study.…”
Section: Antioxidant Capacitiessupporting
confidence: 51%
See 1 more Smart Citation
“…The saturation irradiance for benthic microalgae was low, ranging from 66 to 185 μmol photons m À 1 s À 1 (Guarini et al, 2002;Serôdio et al, 2012). The growth condition was still good for Grammatophora marina when cultured under 180 μmol photons m À 1 s À 1 (Affan et al, 2006). In this study, the P-E curves showed that the E k for phytoplankton at Dm in fall 2013 was 157 μmol photons m À 1 s À 1 .…”
Section: Discussionmentioning
confidence: 76%
“…Isolation of Navicula incerta. The isolation procedure was performed as described in Affan et al. (2006).…”
mentioning
confidence: 99%